Emergence of ESBL-producing Escherichia coli ST131-C1-M27 clade colonizing patients in Europe. (14th August 2018) - Merino, Irene; Hernández-García, Marta; Turrientes, María-Carmen; Pérez-Viso, Blanca; López-Fresneña, Nieves; Diaz-Agero, Cristina; Maechler, Friederike; Fankhauser-Rodriguez, Carolina; Kola, Axel; Schrenzel, Jacques; Harbarth, Stephan; Bonten, Marc; et al.
Abstract: Background: The ST131 Escherichia coli clone is associated with the global dissemination of ESBLs. It has been hypothesized that ST131 could take advantage of better colonizing abilities. However, the data on colonization prevalence of ESBL-ST131 in European hospitals are scarce. Objectives: To assess the prevalence of the ST131 clone and its microbiological characteristics among colonizing ESBL-producing E. coli (ESBL-Ec) from hospitalized patients in four European hospitals (Berlin, Geneva, Madrid and Utrecht) during the R-GNOSIS study. Methods: ESBL-Ec isolates ( n = 688) were obtained from rectal swabs of hospitalized patients from March 2014 to February 2015 using selective media. The ST131 clone and its subclones were sought using PCR and positive isolates were further studied. bla ESBL genes were characterized (PCR and sequencing), antibiotic susceptibility testing was performed, clonal relationships were studied by PFGE and fimH allele and O type (PCR) were assessed. Results: ST131 prevalence was 20.5% (141/688); C1/ H 30R1 isolates were significantly more prevalent in Geneva (49%) and C2/ H 30Rx in Madrid (67%). C1/ H 30R1 isolates showed less resistance to amikacin than C2/ H 30Rx (4% versus 35%) and all were susceptible to penicillin/inhibitor combinations. CTX-M-15 was the most common enzyme (49%) followed by CTX-M-27 (27%). C1/ H 30R1 isolates were significantly associated with CTX-M-27 (72%) and all of these isolates belonged to the C1-M27 clade. Moreover, C2/ H 30Rx isolates and CTX-M-15 were also significantly related (88%). Conclusions: The predominance of C2/ H 30Rx-CTX-M-15 in Madrid and C1/ H 30R1-CTX-M-27 in Geneva demonstrates a changing epidemiology of ESBLs in Europe caused by ST131 subclones; in particular, the emergence of the C1-M27 clade in Europe.